(untitled) (Research, Society and Development, 2021)
Introduction: According to the World Health Organization (WHO), adolescence constitutes a stage of human development and a period of vulnerability for contamination by Sexually Transmitted Infections (STIs), highlighting the Human Papilloma Virus (HPV), which reaches 82 % of adolescents. Objective: To seek to understand the knowledge of high school and public school students about HPV. Method: This is a descriptive, cross-sectional study with a quantitative approach, which took place in two stages, in which 58 students participated. Results: 94.1% answered that they had heard of HPV and 5.9% that they did not. The students’ knowledge about HPV is related to the school environment, since 84.3% reported that they had already had lectures at school. Conclusion: The adolescents’ minimum knowledge about HPV and the importance of the school in the construction of knowledge and health promotion are notorious, as well as the low participation of health units in this process.